Magnetic Sponge with Neutral–Ionic Phase Transitions. Issue 2 (4th December 2017) - Kosaka, Wataru; Takahashi, Yusuke; Nishio, Masaki; Narushima, Keisuke; Fukunaga, Hiroki; Miyasaka, Hitoshi
Abstract: Phase transitions caused by the charge instability between the neutral and ionic phases of compounds, i.e., N–I phase transitions, provide avenues for switching the intrinsic properties of compounds related to electron/spin correlation and dipole generation as well as charge distribution. However, it is extremely difficult to control the transition temperature ( T c ) for the N–I phase transition, and only chemical modification based on the original material have been investigated. Here, a design overview of the tuning of N–I phase transition by interstitial guest molecules is presented. This study reports a new chain coordination‐polymer [Ru2 (3, 4‐Cl2 PhCO2 )4 TCNQ(EtO)2 ]∙DCE (1‐DCE ; 3, 4‐Cl2 PhCO2 − = 3, 4‐dichlorobenzoate; TCNQ(EtO)2 2, 5‐diethoxy‐7, 7, 8, 8‐tetracyanoquinodimethane; and DCE = 1, 2‐dichloroethane) that exhibits a one‐step N–I transition at 230 K (= T c ) with the N‐ and I‐states possessing a simple paramagnetic state and a ferrimagnetically correlated state for the high‐ and low‐temperature phases, respectively. The T c continuously decreases depending on the content of DCE, which eventually disappears with the complete evacuation of DCE, affording solvent‐free compound1 with the N‐state in the entire temperature range (this behavior is reversible). This is an example of tuning the in situ T c for the N–I phase transition via the control of the interstitial guest molecules. Abstract : A chain coordination polymer, exhibiting a one‐step neutral–ionic (N–I) transition is reported. The transition temperature decreases with the gradual evacuation of the crystallization solvent and eventually vanishes. Desolvated compound is neutral in the entire temperature range. The transition behavior is completely recovered by solvent adsorption and therefore the N–I transition synergistically occurs by linking with the degree of solvation.